2016
DOI: 10.1016/j.jval.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Analysis of Prostate Surgery Costs in the United States: Robotic-Assisted versus Retropubic Radical Prostatectomy

Abstract: Monte-Carlo probabilistic sensitivity analysis demonstrated a 38% to 99% probability that RALP provides cost savings (depending on the perspective). Higher surgical consumable costs are offset by a decreased hospital stay, lower complication rate, and faster return to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 104 publications
0
33
0
Order By: Relevance
“…Four studies found a reduced cost for the payer when comparing RARP with RRP. Their results were likely affected by high case volumes for RARP [26], lack of adjustment for patients’ general health status and socioeconomic status [27,28], and assumptions that went into cost modeling [29]. …”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies found a reduced cost for the payer when comparing RARP with RRP. Their results were likely affected by high case volumes for RARP [26], lack of adjustment for patients’ general health status and socioeconomic status [27,28], and assumptions that went into cost modeling [29]. …”
Section: Evidence Synthesismentioning
confidence: 99%
“…While most markups fall into the 1.5–4 range relative to Medicare allowable cost, the markup may be more than 10 times that cost [34]. Finally, three studies constructed models to estimate cost, based on data from the literature and reimbursement rates [29,35,36]. Two of these studies did not perform sensitivity analyses to test how the assumptions would affect cost from the payer’s perspective [29,36].…”
Section: Evidence Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven papers specifically stated other methods of collecting the information on the pathway, which are as follows - [19,22,41,82,116,169] stated that the information was provided to them in some way, [79] through previous work (also consulted with experts and stakeholders), [128] online user input, and [21,24,60] used national guidelines.…”
Section: Obtaining the Pathwaymentioning
confidence: 99%